2002
DOI: 10.1080/08037050213765
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Exercise Attenuates an Exaggerated Exercise Blood Pressure Response in Normotensive Young Adult African-American Men

Abstract: An exaggerated exercise blood pressure response (EEBPR) may be associated with an increased risk of hypertension. We hypothesized that aerobic exercise training can decrease EEBPR and the risk for hypertension by decreasing arterial resistance. We studied the effects of aerobic training on the submaximal exercise blood pressure (BP) of eight normotensive young adult AfricanAmerican men with an EEBPR. Subjects were trained on a stationary bicycle at an intensity of 70% peak oxygen uptake (VO 2peak ) for 30 min,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 18 publications
4
29
0
1
Order By: Relevance
“…However, in a previous study performed in our laboratory, we were able to detect exaggerated blood pressure responses to exercise at 50% VȮ 2peak in African-American men. 32 Prior studies have shown that neither African-American men nor women who are normotensive showed a greater blood pressure response to dynamic exercise than white Americans or Asian-Americans. 33 In that study, the dynamic exercise responses produced significant increments in both systolic and diastolic pressures at 70% of the subjects' VȮ 2 reserve.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a previous study performed in our laboratory, we were able to detect exaggerated blood pressure responses to exercise at 50% VȮ 2peak in African-American men. 32 Prior studies have shown that neither African-American men nor women who are normotensive showed a greater blood pressure response to dynamic exercise than white Americans or Asian-Americans. 33 In that study, the dynamic exercise responses produced significant increments in both systolic and diastolic pressures at 70% of the subjects' VȮ 2 reserve.…”
Section: Discussionmentioning
confidence: 99%
“…This supports previous findings, suggesting that SBP at low-to-moderate exercise intensity correlates with total peripheral resistance, which in turn is associated with underlying vascular properties. 13,14,24 Furthermore, exercise BP has the potential to reveal masked hypertension. 8,9 Future research should compare point estimates and serial measurements of exercise and ambulatory BP both in terms of predictive ability for CV risk and cost-effectiveness.…”
Section: Perspectivesmentioning
confidence: 99%
“…On the other hand, it is possible that high PF and positive ∆PF may modify the increased risk associated with an increase in SBP100W through improving CV risk factors not accounted for in the present study, for example, changes in endothelial properties. 14,24 Measurements of PF require exercise until exhaustion or near exhaustion, often resulting in time-consuming tests and potentially poor patient compliance. Several studies have shown that SBP at low-to-moderate exercise load is more closely associated with future CV risk than SBP measured at submaximal or maximal exercise intensity.…”
Section: Skretteberg Et Al Exercise Blood Pressure Predicts Coronary mentioning
confidence: 99%
“…Algumas alternativas já foram apresentadas na literatura como ferramentas de atenuação da resposta pressórica ao CPT, sendo: 1) Suplementação oral com L-citrulina 22 ; 2) Aplicação de acupuntura 23 ; 3) Uso de fármacos 24 e; 4) Prática de exercícios aeróbios 25 . Quanto ao exercício resistido isotônico à 70%1RM, em nosso conhecimento este é o primeiro estudo a apresentar resultados consistentes de atenuação da resposta pressórica induzida pelo CPT e sendo esta influenciada pelo volume da sessão de exercício resistido.…”
Section: Discussionunclassified